2022
DOI: 10.3390/molecules27072366
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Potential of Adenosine A2A Receptor Antagonists for Treating Parkinson’s Disease

Abstract: The adenosine A2A receptor subtype is recognized as a non-dopaminergic pharmacological target for the treatment of neurodegenerative disorders, notably Parkinson’s disease (PD). The selective A2A receptor antagonist istradefylline is approved in the US and Japan as an adjunctive treatment to levodopa/decarboxylase inhibitors in adults with PD experiencing OFF episodes or a wearing-off phenomenon; however, the full potential of this drug class remains to be explored. In this article, we review the pharmacology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 202 publications
(319 reference statements)
0
9
0
Order By: Relevance
“…It has been reported that OR2W1 could be used as a sensing element in bioelectronic nose to monitor meat quality through hexanal detection (Son et al, 2017). ADORA2A has recently been recognized as an important potential target for treating Parkinson's disease due to its role in regulating the release of glutamate and dopamine (Mori et al, 2022). CXCR2 is associated with many inflammatory diseases including chronic obstructive pulmonary disorder and rheumatoid arthritis, as well as multiple tumor types (Stadtmann & Zarbock, 2012).…”
Section: Functional Production Of At10tagged Gpcrsmentioning
confidence: 99%
“…It has been reported that OR2W1 could be used as a sensing element in bioelectronic nose to monitor meat quality through hexanal detection (Son et al, 2017). ADORA2A has recently been recognized as an important potential target for treating Parkinson's disease due to its role in regulating the release of glutamate and dopamine (Mori et al, 2022). CXCR2 is associated with many inflammatory diseases including chronic obstructive pulmonary disorder and rheumatoid arthritis, as well as multiple tumor types (Stadtmann & Zarbock, 2012).…”
Section: Functional Production Of At10tagged Gpcrsmentioning
confidence: 99%
“…A 2A R modulates glutamatergic synaptic transmission in the CNS, and acts on microglia and astrocyte activation, exerting a pivotal role in neurodegenerative diseases, including AD, particularly regulating neuroinflammation via inhibition of NLRP3 inflammasome (a tripartite multiprotein complex including NLRP3, ASC, and procaspase-1; Merighi et al., 2022a ; for recent reviews see Merighi et al., 2022b , 2022c ). A selective A 2A R antagonist (istradefylline) is already approved in the US and Japan as an adjunctive treatment to levodopa and decarboxylase inhibitors in patients with Parkinson's disease (for a recent review see Mori et al., 2022 ) and this antagonist has been investigated as a putative candidate for the treatment of AD as well; if its effects on AD is confirmed and reproducible, a new hope for AD patients is coming ( Merighi et al., 2022a ; for recent reviews see Merighi et al., 2022b , 2022c ). Carrier et al.…”
Section: Relationships Among the Gut Microbiota Intestine And Brainmentioning
confidence: 99%
“…In particular, the A 2A subtype is localized in the basal ganglia where it is also co-expressed with the dopamine D2 receptor and its blockade enhances D2 receptor function [ 16 ]. For this reason, A 2A AR antagonists emerged as a nondopaminergic therapy for Parkinson’s disease (PD) [ 17 ] leading to the commercialization of the A 2A AR antagonist istradefylline as an adjunctive therapy for the treatment of patients suffering with this pathology [ 18 ].…”
Section: Introductionmentioning
confidence: 99%